Islamic Philanthropy : Waqf Empowerment of Madina Minimarket In Tasikmalaya - Indonesia - Suryanto, Asep -; Zulfikri Rahmat, Biki; Marlina, Lina (Universitas Islam Negeri Raden Intan Lampung, 2020)
The purpose of this study was to determine the implementation of productive waqf economic empowerment in the form of a minimarket in Purbaratu, Tasikmalaya City. Grouded research used to try to develop a concept through empirical exploration of the economic empowerment of productive endowments carried out by the City of Tasikmalaya Baznas so as to produce a conceptual description of the economic empowerment of productive waqf. The results showed that the Madina minimarket is an implementation of empowering productive waqf through business activities with the concept of the people for the people (social enterprise). Madina Minimarket is built on waqf land given by waqif to the Baznas Tasikmalaya City is used as fixed capital for minimarkets while working capital is obtained from investors. Every month, the profit earned by Madina minimarket is used to pay the minimarket employees and distributed to all mosques in Purbaratu District neighborhood in the form of shopping vouchers for mosque needs.Keywords : IslamicPhilanthropy, Empowerment, Waqf